STRATEGIC SYNERGY AND PRIVATE SOCIAL INVESTMENT: AN ANALYSIS OF SDG INTEGRATION WITHIN NEOENERGIA’S ESG+F MODEL (REMUNOM, 2026)
This study analyzes the strategic integration of Private Social Investment (PSI) by the Neoenergia Institute with the social axis of the Group's ESG+F (Finance) commitment, through the lens of Shared Value creation. The research investigates how social actions transcend traditional philanthropy to become strategic corporate assets aligned with the 2030 Agenda. Given the normative relevance of ABNT PR 2030, the work examines the synergy between Neoenergia's priority Sustainable Development Goals (SDGs) and global sustainability targets. The methodology is based on a qualitative, exploratory, and descriptive approach, utilizing document analysis of institutional reports (2022-2024) and the application of the SDG Compass protocol. The results demonstrate that PSI acts as a catalyst for corporate sustainability, enabling the integration of territorialized social performance with the Group's financial rating. The study concludes that the Neoenergia Institute plays a fundamental role in impact governance, establishing social value creation as a competitive advantage for sustainable development and the maintenance of the Social License to Operate.